Neonatal sepsis for postpartum depression - Chintha Jayasinghe; Chrisantha Abeysena (College of Community Physicians of Sri Lanka, 2019)
Introduction: The postpartum period is generally a time of happiness and bonding between mother and the newborn, but complicated pregnancies can alter this. Postpartum depression (PPD) is a common complication of childbirth.   Objectives: To determine the effect of neonatal sepsis on PPD of mothers   Methods: This was a descriptive study conducted in secondary and tertiary care hospitals in the district of Gampaha. The study population comprised postpartum mothers of neonates who were diagnosed with sepsis (n=236) and those who were not (n=240). Neonatal sepsis was defined by the presence of one of the clinical signs according to the IMCI strategy or culture positive blood or cerebrospinal fluid. The validated Edinburgh Postpartum Depression Scale and an interviewer-administrated questionnaire were used. Multiple logistic regression was applied and adjusted odds ratios (aOR) and 95% confidence intervals (CI) were calculated.   Results: The study revealed that among the mothers of sepsis neonates, 185 (78.4%) were depressed. There were 51 (21.2%) mothers also depressed among the mother of non-sepsis babies. The association between PPD and neonatal sepsis was statistically significant (aOR=13.44; 95% CI=8.68, 20.83). The socio-demographic factors, obstetric and neonatal factors were not independently associated with PPD.   Conclusions: Postpartum depression among mothers of sepic neonates was higher than in mothers of apparently healthy neonates. It is essential to arrange a screening programme and counselling sessions while in the hospital for all the mothers.